Registration of voice quality - Frøkjær-Jensen, Børge; Prytz, Svend (Annual Report of the Institute of Phonetics University of Copenhagen, 1975)
Long-time average-spectra recordings of normal voices as well as an average spectrum of such LTAS-registrations are shown and discussed. For comparisons of voice qualities we have tried to set up a new parameter, α, which is a measure of the intensity relations in the higher and the lower parts of the speech spectrum: α = intensity above 1000 Hz / intensity below 1000 Hz. Because the spectrum above 1000 Hz is normalized relative to the spectrum below 1000 Hz, α is independent of microphone distance, amplification level, etc. α seems to be a good acoustic correlate to the physiological term "medial compression", and preliminary research indicates that it is relevant to evaluations and comparisons of voice qualities. The "quality parameter" is represented graphically by histograms showing the number of α-values automatically sampled during a read text, and it is displayed on a storage oscilloscope along the vertical axis. The horizontal axis is used for displaying the total speech intensity.